Are better existing WASH practices in urban slums associated with a lower long-term risk of severe cholera? A prospective cohort study with 4 years of follow-up in Mirpur, Bangladesh. Issue 9 (21st September 2022) - Kang, Sophie; Chowdhury, Fahima; Park, Juyeon; Ahmed, Tasnuva; Tadesse, Birkneh Tilahun; Islam, Md. Taufiqul; Kim, Deok Ryun; Im, Justin; Aziz, Asma Binte; Hoque, Masuma; Pak, Gideok; Khanam, Farhana; et al.
Abstract : Objective: To investigate the association between existing household water quality, sanitation and hygiene (WASH) practices and severe cholera risk in a dense urban slum where cholera is highly endemic. Design, setting and participants: We assembled a large prospective cohort within a cluster randomised trial evaluating the effectiveness of oral cholera vaccine. Our dynamic cohort population (n=193 576) comprised individuals living in the 'non-intervention' clusters of the trial, and were followed over 4 years. This study was conducted in a dense urban slum community of Dhaka, Bangladesh and cholera surveillance was undertaken in 12 hospitals serving the study area. Primary outcome measure: First severe cholera episode detected during follow-up period. Methods: We applied a machine learning algorithm on a training subpopulation (n=96 943) to develop a binary ('better', 'not better') composite WASH variable predictive of severe cholera. The WASH rule was evaluated for performance in a separate validation subpopulation (n=96 633). Afterwards, we used Cox regression models to evaluate the association between 'better' WASH households and severe cholera risk over 4 years in the entire study population. Results: The 'better' WASH rule found that water quality and access were the most significant factors associated with severe cholera risk. Members of 'better' WASH households, constituting one-third of the population, had a 47% reduced risk of severe cholera (95% CI: 29 to 69; p<0.001), after adjusting for covariates. The protective association between living in a 'better' WASH household and severe cholera persisted in all age groups. Conclusions: Salutary existing household WASH practices were associated with a significantly reduced long-term risk of severe cholera in an urban slum of Dhaka. These findings suggest that WASH adaptations already practised in the community may be important for developing and implementing effective and sustainable cholera control programmes in similar settings. Trial registration number: This article is a re-analysis of data from a cluster randomized trial; can be found on ClinicalTrials.gov NCT01339845